PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA TOKO SEPATU BATA MTC GIANT PANAM PEKANBARU - Rachel Florencia Simatupang; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The sucess of company depends on several interrelated components and supporting each other. The components are product quality, price and customer satisfication. This research was conducted at Bata Shoes Store MTC Bata Giant Panam Pekanbaru. The problem in this research is the sale of Bata’s shoes was fluctuated and tenden to decline each year, and does not even rreach the sales target. Seen from the presentation realization sale product of a shoes in the last 5 years. As for the purposeof this study was to determine the influence of product quality and price on customer satisfication at Bata Shoes Store MTC Giant Panam Pekanbaru. Product quality and price as the independent variable (  while the customer satisfication as the dependent variable (Y). The research sample was taken of 100 respondents of the population was calculated using the Slovin formula. The data was gettig from the questionnaire and subsequently processed to then be tested with statistics through SPSS. From the results which shows that product quality and price have a positive and significant impact on customer satisfication at Bata Shoes Store MTC Giant Panam Pekanbaru.                                      Key words: Store Location, Promotion, Consumer Buying Interest